The use of activity diaries for understanding the daily lives of farmers and their livelihood choices - Apis, B.; Aranka, J.; Asiota, B.; Bafeo, M.; Bekio, J.; Bore, W.; Curry, George; Hamago, M.; Inu, S.; Kiup, E.; Koczberski, Gina; Lummani, Joachim; et al. (Australian Centre For International Agricultural Research (ACIAR), 2013)
This paper reviews the use of activity diaries in two Australian Centre for International Agricultural Research (ACIAR) projects in PNG: a smallholder cocoa project in the East New Britain province (ASEM/2006/127) and a smallholder coffee project in Eastern Highlands province (ASEM/2008/036). Both projects were similarly concerned with identifying the production constraints on cocoa- and coffee-farming households and to better understand the range of socioeconomic and cultural factors influencing farmer decision-making and the allocation of household labour among various livelihood activities. In PNG, the household is the principal production unit underpinning livelihood activities such as commodity production. It is at the household level that decisions and negotiations are made regarding the organisation, mobilisation and management of family and extended family labour. Thus, examining in detail the daily economic and social livelihood activities of household members, through time-allocation studies, helps researchers to understand more comprehensively the factors influencing smallholder decision-making regarding livelihood choices, agricultural practices and the adoption of agricultural innovations. This paper outlines two different techniques using activity diaries employed in the projects, and discusses the methodological advantages and challenges of these techniques in smallholder studies in PNG.